PSMA PET/CT vs. CT alone in newly diagnosed biochemical recurrence of prostate cancer after radical prostatectomy: Comparison of detection rates and therapeutic implications. Issue 136 (March 2021) - Morawitz, J.; Kirchner, J.; Lakes, J.; Bruckmann, N.M.; Mamlins, E.; Hiester, A.; Aissa, J.; Loberg, C.; Schimmöller, L.; Arsov, C.; Antke, C.; Albers, P.; et al.
Highlights: PSMA PET/CT is superior to CT on a per-patient and per-lesion basis in biochemically recurrent prostate cancer patients. PSMA PET/CT enables the detection of significantly more metastases than CT alone. Higher detection rate with PET/CT translates into therapy-change in many patients. CT alone seems insufficient for re-staging of biochemically recurrent prostate cancer. Abstract: Objectives: To compare prostate specific membrane antigen (PSMA) Positron Emission Tomography/Computed Tomography (PET/CT) and computed tomography (CT) alone for the detection of biochemical recurrence of prostate cancer (PCa) and effect on treatment. Methods: This retrospective study included 59 patients with recently recorded biochemical recurrence of PCa (mean PSA 1.96 ± 1.64 ng/mL) after radical prostatectomy. Patients received PET/CT with either 68 Ga-PSMA-11 (n = 36) or 18 F-PSMA-1007 (n = 23). PET/CT and CT images were evaluated separately in regard to PCa lesion count, type, and localisation by two physicians. Histopathology, follow-up imaging and PSA levels after salvage irradiation served as reference standard. A McNemar test was used to compare detection rates. Changes in therapeutic approaches based on staging differences between CT alone and PET/CT were assessed in a virtual multidisciplinary tumour board. Results: There were 142 lesions in 50 of 59 patients. PSMA PET/CT detected 141 lesions (99.3 %) in 50 patients (84.7 %), while CT detected 72 lesions (50.7 %) in 29 patients (49.2 %). A significantly higher detection rate of PSMA PET/CT was observed on a lesion-based analysis (p < 0.0001) and on a patient based analysis (p < 0.0001). Herein, both 68 Ga- and 18 F-PSMA PET/CT performed significantly better than CT alone (p < 0.0001, respectively). In 9 patients (15.3 %) no relapse was detectable by either modality. All lesions detected by CT were also detected by PSMA PET/CT. In 38 patients PSMA PET/CT detected more lesions than CT alone, altering the treatment approach in 22 of these patients. Conclusion: PSMA PET/CT is superior to CT alone in detecting biochemical recurrence in PCa patients after radical prostatectomy and offered additional therapeutic options in a substantial number of patients.